2021
DOI: 10.31083/j.ceog.2021.01.2228
|View full text |Cite
|
Sign up to set email alerts
|

Difference between near-field and far-field of middle cerebral artery doppler pulsatility index and peak systolic velocity: a prospective study

Duygu Adıyaman,
Bahar Konuralp Atakul,
Melda Kuyucu
et al.

Abstract: We purposed to investigate the di ference between nearfield and far-field of PI (pulsatility index) and peak systolic velocity (PSV) of the middle cerebral artery (MCA) that are important in the management of fetal growth restriction and fetal anemia. Methods: This prospective study was conducted with 130 single uncomplicated pregnancies. Doppler was applied to near-and far-field of proximal MCA while PSV and PI were recorded and compared between two sides as well as according to body mass index (BMI) and gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Intracranial artery stenosis/occlusion mainly caused by intracranial atherosclerosis is an important factor causing ischemic brain disease and an independent factor inducing stroke recurrence ( Holmstedt et al, 2013 ). Currently, TCCD, as the most widely applied method to detect cerebral artery, can examine the degree of stenosis/occlusion of the proximal middle cerebral artery (MCA), anterior cerebral artery, posterior cerebral artery, basilar artery, and bilateral vertebral arteries (VA) by non-invasive, continuous monitoring of the CBV ( Finnsdottir et al, 2020 ; Spence, 2020 ; Adıyaman et al, 2021 ). Additionally, compared with the anterior circulation, there is greater tortuosity and variability in the posterior circulation; predictably, the sensitivity and specificity of TCCD are higher in the anterior circulation ( Jaiswal et al, 2019 ).…”
Section: Clinical Application Of Transcranial Dopplermentioning
confidence: 99%
“…Intracranial artery stenosis/occlusion mainly caused by intracranial atherosclerosis is an important factor causing ischemic brain disease and an independent factor inducing stroke recurrence ( Holmstedt et al, 2013 ). Currently, TCCD, as the most widely applied method to detect cerebral artery, can examine the degree of stenosis/occlusion of the proximal middle cerebral artery (MCA), anterior cerebral artery, posterior cerebral artery, basilar artery, and bilateral vertebral arteries (VA) by non-invasive, continuous monitoring of the CBV ( Finnsdottir et al, 2020 ; Spence, 2020 ; Adıyaman et al, 2021 ). Additionally, compared with the anterior circulation, there is greater tortuosity and variability in the posterior circulation; predictably, the sensitivity and specificity of TCCD are higher in the anterior circulation ( Jaiswal et al, 2019 ).…”
Section: Clinical Application Of Transcranial Dopplermentioning
confidence: 99%
“…Two large foreign studies, Action to Control Cardiovascular Risk in Diabetes -Blood Pressure (ACCORD-BP) and Systolic Blood Pressure Intervention Trial (SPRINT), showed that improving blood pressure can reduce the incidence of cardiovascular events, while other Chinese scholars' studies also reached the same conclusion. Therefore, the reasonable intervention of T2DM blood pressure is a necessary measure to prevent CVDs (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia is an essential procedure for mammal experiment. Inappropriate anesthesia may result in near-death state among mammals, which affects experimental results [3][4][5] . Therefore, safer anesthesia methods should be adopted to promote anesthesia techniques and reduce experimental costs.…”
mentioning
confidence: 99%